2022
DOI: 10.1038/s41698-022-00271-x
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of genomic loss of heterozygosity in leiomyosarcoma are distinct from carcinomas

Abstract: Leiomyosarcoma (LMS) is a rare, aggressive, mesenchymal tumor. Subsets of LMS have been identified to harbor genomic alterations associated with homologous recombination deficiency (HRD); particularly alterations in BRCA2. Whereas genomic loss of heterozygosity (gLOH) has been used as a surrogate marker of HRD in other solid tumors, the prognostic or clinical value of gLOH in LMS (gLOH-LMS) remains poorly defined. We explore the genomic drivers associated with gLOH-LMS and their clinical import. Although the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Genomic alterations in BRCA1/2 have been highly associated with HRD in many cancers [25,38]. Sokol et al showed that a BRCA1/2 alteration was consistently associated with LOH-high in many cancer types, including breast cancer, and the magnitude was variable for each cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic alterations in BRCA1/2 have been highly associated with HRD in many cancers [25,38]. Sokol et al showed that a BRCA1/2 alteration was consistently associated with LOH-high in many cancer types, including breast cancer, and the magnitude was variable for each cancer type.…”
Section: Discussionmentioning
confidence: 99%
“…This study is reported in accordance with the Strengthening the Reporting of Genetic Association Studies ( STREGA ) reporting guideline [12] . Genomic profiling data from EWSR1 fusion positive tumors was collected as assayed during clinical care using FMI's hybrid-capture-based next-generation sequencing (NGS) platform as previously described [13] , [14] , [15] . Approval for the retrospective collection of genomic data from FMI, including a waiver of informed consent and a HIPAA waiver of authorization, was obtained from the Western Institutional Review Board (protocol: 20,152,817).…”
Section: Methodsmentioning
confidence: 99%
“…At this point, it is important to highlight the need to establish predictive markers of response to systemic therapies, especially for patients who do not respond to standard chemotherapy. Research is being conducted into genomic profiling of uterine and non-uterine LMS [9][10][11] which will support the identification of targeted therapies for patients who currently have no adequate treatment options.…”
Section: Case Reports In Oncologymentioning
confidence: 99%